From Carbon Footprint to Social Justice: Rethinking Sustainability in Television Production and Virtual Studios - Jayaraj, Anee; Ghodt, Isabell Hersleb (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
The environmental and social impacts of television drama productions are staggering, with a single hour-long episode generating an average carbon footprint of 77 metric tonnes, equivalent to driving a car around the world six times. Key contributors include extensive fuel consumption (58% of emissions), air travel, energy use, and accommodation. This research explores the integration of environmental and social sustainability practices across diverse filming contexts, addressing the absence of clear, adaptable guidelines for production teams. There is clear evidence for pushing the integration of sustainability practices in the entertainment industry. However, the lack of research in this field is a challenge. What is the climate impact of the various production operations? What are the greener choices? And what about diversity, health and safety, and workers’ unions? When every production is unique, how does one know the best option for sustainability? This research aims to advance environmental and social sustainability integration across various departments and production locations. This research project addresses the lack of concise and clear sustainability guidelines tailored to each filming department and adaptable to multinational productions. A multinational project team of academics and practitioners from five countries simulated the monetary and environmental costs of filming a six-episode television period drama set in both Denmark and Argentina. The simulations assessed the effectiveness of the proposed environmental and social sustainability guidelines across the different production methodologies. Some early adopters and industry experts suggest that virtual production could enhance crew diversity and mitigate biodiversity loss within the entertainment sector. This belief has driven significant investment in costly virtual production studios across Europe. However, these claims remain largely theoretical, lacking robust empirical validation. To bridge this gap, this project undertakes the world’s first large-scale investigation to quantify and qualify the environmental and social impacts of virtual production, providing data-driven insights into its true potential for sustainable filmmaking. DISCLAIMER: At the time of writing this text, final results have not yet been obtained from the research.